Assessment of micro and macroplastics along the west coast of India: Abundance, distribution, polymer type and toxicity. (May 2020) - Maharana, Dusmant; Saha, Mahua; Dar, Jaffer Yousuf; Rathore, Chayanika; Sreepada, R.A.; Xu, Xiang-Rong; Koongolla, J. Bimali; Li, Heng-Xiang
Abstract: Considering the magnitude of pollution caused by marine plastics, the present study assessed their abundance, distribution, surface morphology and polymer type in ten sandy beaches spread across three states (Maharashtra, Karnataka and Goa) along the west coast of India (WCI). The total abundance of plastics (∼1–100 mm) in the studied beaches ranged from 4.1 to 23.4% (19±1–346 ± 2 items/m 2 ). Location-wise, the abundances of both micro (43.6 ± 1.1–346 ± 2 items/m 2 ) and macroplastics (21.6±3–195 ± 6 items/m 2 ) were relatively higher in beaches along the Maharashtra coast. Surface morphology-wise, fragments were predominantly abundant in both micro (76±2–346 ± 2 items/m 2 ) and macroplastics (50.6 ± 1.5–195 ± 6 items/m 2 ) followed by pellets (43.3 ± 2.5–245.6 ± 2 items/m 2 ). Fourier-transform infrared spectroscopy (FT-IR) analysis of plastics revealed a dominance of polyethylene (PE) followed by polypropylene (PP). IR spectra of the collected plastics at absorption band at 1750–1700 cm −1 reflect minimal surface oxidation. White-colored plastics were observed most frequently, followed by pale-yellow, dark-brown, green, blue, transparent and red. A short-term (72 h) experimental study to assess the toxicity of PE microbeads (∼1 mm) in a commercially important shrimp species, Litopenaeus vannamei revealed toxicological changes. An elevated level of lipid peroxidation (LPX)—the tagged biochemical marker, was recorded only at the maximum dose (0.15 mg/L) of PE microbeads. A moderate increase in the levels of enzymatic antioxidants (catalase and glutathione S-transferase) was also recorded at the same dose. Comprehensive information on marine plastics, including ecotoxicity provided in this study, would help in evolving strategies in minimizing plastic pollution along the WCI. Graphical abstract: Image 1 Highlights: A relatively high abundance of plastics recorded on most popular beaches along the west coast of India. Surface morphology-wise, fragments followed by pellets were the most abundant plastic items. Amongst diverse plastic items, white-colored polyethylene polymers dominated. Toxicological changes in Litopenaeus vannamei were recorded at the highest exposure dose of PE microbeads.